Longarm and The Longley Legend - Evans, Tabor (New York Jove Books, 1990)
When a fellow lawman is shot dead, Marshall Long is sent to hunt down the culprit. But this bedsheet-wearing bandit is no run-of-the-mill robber. Some folks claim he's the legendary Wild Bill Longley. Others think he's Longley's son or his ghost.
Keywords: Longarm (Fictitious character) -- Western stories